2021
DOI: 10.1177/2333794x21999154
|View full text |Cite
|
Sign up to set email alerts
|

An Increased Adverse Fetal Outcome Has Been Observed among Teen Pregnant Women in Rural Eastern Ethiopia: A Comparative Cross-Sectional Study

Abstract: Background: According to the World Health Organization, teenage pregnancies are high-risk due to increased risks of fetal and infant morbidity and mortality. This study compares adverse fetal outcomes between teen and adult pregnant women from rural Eastern Ethiopia. Methods: Institutional-based cross-sectional study was conducted among women visiting maternity units from surrounding rural areas. A total of 481 teenagers (13-19 years old) and 481 adults (20-34 years old) women with a singleton pregnancy were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…The WHO views teenage pregnancies as high-risk pregnancies because they are linked to unfavorable outcomes for both mother and foetus [9]. Adolescent pregnancy is highly correlated with early sexual activity [10].…”
Section: Methodsmentioning
confidence: 99%
“…The WHO views teenage pregnancies as high-risk pregnancies because they are linked to unfavorable outcomes for both mother and foetus [9]. Adolescent pregnancy is highly correlated with early sexual activity [10].…”
Section: Methodsmentioning
confidence: 99%
“…Complications of maternal and neonatal are also increased in adolescents due to many reasons such as the immaturity of the pelvis and nutritional insufficiency (8) A prospective cohort research exploring the association between maternal growth and outcomes revealed that sustained maternal growth in adolescent altered nutritional partitioning between maternal and fetal, which had a detrimental impact on fetal growth and preterm (9) .…”
Section: Introductionmentioning
confidence: 99%